Once upon a time... you! A game to support health professionals in the treatment of children with chronic diseases, helping them to express their feelings - Verhalen, Aline Elias Cardoso; Silva, Tiago Marino; Rodrigues, Kamila Rios Da Hora (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Serious games are being used in many areas to develop skills in target users. In the Health area, serious games are used to help patients understand procedures that they are applied during the treatments. When the patient is a child, the game can help her/him understand the treatment, beyond entertainment. This paper describes a serious game designed with the support of Health professionals, with the aim of supporting the treatment of children with chronic and lifethreatening illnesses. An approach to designing therapeutic games was used to create the game. This approach provides techniques and artifacts to idealize, model, prototype, and evaluate a therapeutic game. The game was called “Inverted Narrative” because the child will elaborate the narrative from pre-available game elements, such as speech bubbles, objects, and characters. The purpose of the game is to allow children to express their feelings through the created story and for Health professionals to use this artifact with therapeutic resources to initiate a dialogue or a therapeutic procedure. Using empirical methods, the game was evaluated at two different moments, with different audiences. The evaluations pointed to improvements related to gameplay and accessibility.